PENGEMBANGAN E-LKPD MATERI BILANGAN PECAHAN BERBASIS PROBLEM BASED LEARNING PADA KELAS IV SEKOLAH DASAR - Yunita Triwiyanti Pribadi; Dudung Amir Sholeh; Yetty Auliaty (Program Studi PGSD Universitas Flores, 2021)
Student worksheet usually in printed form, while Electronic student worksheet in digital form, so it could be accessed anywhere using the internet network. This study aims to develop and determine suitability of Electronic worksheets on fractional number material in grade 4th. Type of research is R&D using the 4-D Thiagarajan and Sammel model which consists of four step, 1) Define, 2) Design, 3) Develop, 4) Disseminate. The subjects of this research were 4th grade students of SDN Menteng Atas 01 Pagi. Data instruments in the form of observations, interviews, expert review and student response questionnaires. The expert review process is carried out on material, media, and language experts. The average result of the three experts is 86.20% and can be interpreted as